A mini review: Lean management tools in assembly line at automotive industry - M. Z. M., Ismail; A. H., Zainal; Nazrul Idzham, Kasim; M. A. F. M., Mukhtar (IOP Publishing, 2019)
Malaysia is active in automotive manufacturing activity for decades. The needs in continuing development of lean manufacturing tools are not exempt to be pressurised, which enable the regional demand for vehicles. Several research studies clearly indicate significant opportunities for efficiency improvement in the automotive industry through implementation and a higher level of lean management utilization. Apparently, there is still a small number of study for Lean Management Tools in a Malaysian Automotive Assembly Line. The emphasis for the study is to investigate practices of lean tools applied in the production line and proposing an implementation of lean management tools available to apply in the Malaysian automotive production line work practice. A review study of literature from different journal publication sources related to lean management tools was made to understand more on how to best identify practices of lean tools. From this literature study review, three lean management tools have been investigated and identified such as 5S, Value Stream Mapping (VSM) and Work Standardization are to be studied for proposed application in the Malaysian automotive assembly production line. The impact of implementing lean tools is studied based on the results gathered from previous studies related to 5S, VSM and Work Standardization. The conclusion of this paper is to investigate the practices and implementation of Lean Management Tools in the Malaysian Automotive Assembly. It is to be suggested that a future case study on the proposed lean tools using time study and observational survey to be implemented in Malaysian automotive assembly line and measuring the improvements gained from utilizing the selected lean tools. The result from this review is that among the lean tools highlighted here, 5S is applied everywhere in an automotive assembly line, supported by VSM with its overview of the whole process and also Work Standardization to standardize the method and flow of work in an assembly line and improve the consistency of work. Therefore, concluding this study would be the importance of 5S, VSM and Work Standardization as the implemented tools in an automotive assembly line, in view of overcoming the challenges of the constant change in customer demand.